The use Barthel Index in brazilian elderly: a literature review - Araujo, Elloí Anunciada Tinôco (2020)
The objective was to identify the population niches of elderly people who were interviewed with the Barthel Index in the national scientific scenario. It is a review of scientific literature of the narrative type, with articles selected from 2008 to 2018 in the following databases: LILACS, BVS, and the CAPES Journal Portal. 57 articles were found, but only five were part of this research. The instrument in question was validated for a sample of elderly outpatients, but it was used for the elderly in different social niches.